Gastroduodenal Mucosal Integrity and Influencing Factors - Dadang Makmun (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2005)
Gastroduodenal mucosal integrity has important role in the pathogenesis of gastroduodenal ulcer. It depends on imbalance between aggressive and defensive factors. However, many experts believe that defensive factors has more dominant role. Maintenance of gastrointestinal endothelial integrity appears to define the “cytoprotection” phenomenon and, as discussed below, is a critical component of NSAID- induced GI injury and a potential target for therapeutic intervention. Keywords: mucosal integrity, aggressive factors, defensive factor, cytoprotection